2017
DOI: 10.1021/acsphotonics.6b00999
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Resolved Observation of the Gouy Phase Shift of Surface Plasmon Polaritons

Abstract: The space-resolved Gouy phase shift for focused surface plasmon polaritons (SPPs) in the optical regime is experimentally demonstrated for the first time. SPPs are excited by CW laser radiation focused onto a dielectric ridge placed on a cover glass surface coated by a silver film. The Gouy phase measurements are performed using interference between a reference plane wave and leakage radiation. The measured Gouy shift has a value of π/2 corresponding to the two-dimensional nature of surface plasmon polaritons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Note added in proof. When completing our work, we found that the Gouy phase shift of PGBs has been measured and reported using LRM with phase detection [16].…”
Section: Acknowledgmentsmentioning
confidence: 91%
“…Note added in proof. When completing our work, we found that the Gouy phase shift of PGBs has been measured and reported using LRM with phase detection [16].…”
Section: Acknowledgmentsmentioning
confidence: 91%
“…The azimuthal mode number is dropped with 0 throughout (i.e., pure radial LG beams with radial number ). For a given optical frequency, the phase of the field relative to that of a plane wave propagating along [i.e., the Gouy phase ( 20 22 )] is given by , with the Rayleigh range .…”
Section: Lg Superpositions In the Paraxial Limitmentioning
confidence: 99%
“…However, 4 microscopy requires interferometric stability and delicate mode matching. Another method relies on copropagating beams each with distinct Gouy phases ( 20 22 ), which was proposed and realized mostly in the context of dark (i.e., blue-detuned) optical traps, either with two Gaussian beams of different waists or offset foci ( 23 , 24 ) or with LG modes of different orders ( 14 , 25 ). However, for bright (i.e., red-detuned) trap configurations, a comparable strategy has remained elusive.…”
mentioning
confidence: 99%
“…In other words, these boundaries between two antiparallel noncentrosymmetric domains present strains and perturbations of the refractive index. Additionally, these imperfections are randomly positioned and if they are limited to the nanoscale, they will produce a local-field enhancement as described in [48][49][50]. This enhancement can be up to 10 times or more [51,52] and leads to "hotspots" that have already been observed even in centrosymmetric materials that present local defects [53].…”
Section: Ppln: Removing Incoherent Imaging Artifactsmentioning
confidence: 99%